Safety of Laparoscopic Splenectomy for Patients with Idiopathic Thrombocytopenic Purpura and Very Low Platelet Count - Abbas Abdollahi; Seyed Maryam Naghibi; Hamed Shariat Razavi; Alireza Tavassoli; Azadeh Jabbari Nooghabi; Mehdi Jabbari Nooghabi (Babol University of Medical Sciences, 2022)
Background: Chronic idiopathic thrombocytopenic purpura (ITP), is an autoimmune disease associated with a reduction in circulating blood platelets under 150x109/L which persists longer than 6 months without any specific cause. With the current study, we aimed to evaluate the efficacy and safety of laparoscopic splenectomy in ITP patients with a very low platelet count and normal coagulation status. Methods: From April 2007 to January 2012, laparoscopic splenectomy was performed on 60 patients with chronic ITP who could not achieve a sustained recovery after steroid therapy. Results: Patients consisted of male/female ratio of 24 (40%):36 (60%) with the mean age of 53±15.1 years. All patients had normal coagulation state even with very low platelet count (below 5×103) before laparoscopic splenectomy. The mean operative time was 140.00±15.00 minutes. Blood transfusion was required in 10 (16.7%) and 8 (13.3%) patients before and after the operation, respectively. Preoperative transfusion of PRBC was not statistically significant between groups (P=0.265). Bleeding complications during within or after surgery was rare (5.0%). Convalescence was rapid and the mean hospital stay was 3.58±0.68 days (1-14 days) which shows that there was no significant difference in operative time and after operative hospitalization time among the three groups (P=0.070). The patients made a good uneventful recovery and were followed for at least one week who exhibited no postoperative problems. Conclusion: Laparoscopic splenectomy should be considered initially in the management of ITP. Also, very low platelet count should not be contraindicated for laparoscopic splenectomy in ITP patients and sometimes perioperative platelet transfusion may be unnecessary.